Assessment of genetic diversity in relation to seed yield and its component traits in Indian mustard (Brassica juncea L.) - Sanghamitra Rout; SA Kerkhi; Pooran Chand; SK Singh (Journal of Oilseed Brassica, 2026)
The genetic divergence were tested of thirty eighty genotypes of Indian mustard (Brassica juncea L.) in randomizedblock design with three replications during Rabi 2015-16. Observations were recorded for twelve characters viz., days to50% flowering, days to maturity, number of primary branches per plant, number of secondary branches per plant, numberof siliqua per plant, plant height (cm), number of seeds per siliqua, siliqua length (cm), biological yield per plant (g),harvest index (%), seed yield per plant (g) and 1000-seed weight (g). Genetic divergence was studied using MahalanobisD2 statistics. Genotypes were grouped into seven clusters. The I (eight genotype) and II (eight genotype) cluster havingthe maximum number of genotypes followed by cluster IV (seven genotype), V & VI have (five genotype) each, III (threegenotype) and VII (two genotype). Maximum average intra cluster divergence value was found for cluster VII andminimum intra cluster divergence value was found for cluster V. Maximum inter cluster D2 value was recorded betweencluster VII and VI where as minimum inter cluster distance was observed between cluster II and cluster I. Based on thelarger intra cluster distance value, the crosses could be made among the genotypes (PBR-210 & Sanjucta ASECH) with(RLM- 619, Pusa Tarak, Jawahar mustard, Swarnajyoti & RGN-73) for obtaining useful progenies in the segregatinggeneration and also for development of hybrids in mustard. The characters biological yield per plant (g), number ofsiliquae per plant, number of seeds per siliqua, siliqua length (cm), days to 50% flowering and1000-seed weight (g)contributed more than 90.8 % of the total genetic diversity.